Experimental Study of the Sensitive Element of the Angular Velocity Sensor on Bulk Acoustic Waves - Durukan, Yasemin; Popkova, Ekaterina S.; Peregudov, Alexandr N.; Shevelko, Michail M. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2022)
The paper describes the developed prototype of the sensitive element of the angular velocity sensor based on bulk acoustic waves and presents the results of its experimental studies. The plate piezoelectric transducers of the sensing element are made of PZT-4 piezoceramics with an operating frequency of 0.5 MHz, and the acoustic duct is made of fused quartz. An informative parameter of the sensitive element is the value of the orthogonal component of the polarization vector, which is proportional to the angular velocity of the object rotation. The article represents a new method for measuring the angular velocity, based on the results of the research. The impact of rotation on the sensitive element is estimated for the case of an arbitrary oriented rotation axis. The informative parameter is estimated to be the value of the rotation angle for the polarization vector in the emitted shear wave. Further directions to develop the discussed scientific field and application area are suggested.